2014
DOI: 10.1063/1.4897378
|View full text |Cite
|
Sign up to set email alerts
|

Growth of silicon quantum dots by oxidation of the silicon nanocrystals embedded within silicon carbide matrix

Abstract: Articles you may be interested inPhotoluminescence properties and crystallization of silicon quantum dots in hydrogenated amorphous Si-rich silicon carbide films Effect of thickness on the photoluminescence of silicon quantum dots embedded in silicon nitride films Low-temperature synthesis of homogeneous nanocrystalline cubic silicon carbide films J. Appl. Phys. 102, 056101 (2007); 10.1063/1.2776155 H-induced effects in luminescent silicon nanostructures obtained from plasma enhanced chemical vapor deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…That oxygen group could be formed as silicon dioxide. According to XPS data silicon dioxide was formed on silicon wafer after GO reduction as shown in Si 2p spectrums ( figure S10 ) 72 . The SiO 2 peak (103.65 eV) was found after GO reduction process.…”
Section: Discussionmentioning
confidence: 99%
“…That oxygen group could be formed as silicon dioxide. According to XPS data silicon dioxide was formed on silicon wafer after GO reduction as shown in Si 2p spectrums ( figure S10 ) 72 . The SiO 2 peak (103.65 eV) was found after GO reduction process.…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectrum of rGO-Si nanocomposite ( Figure 1 b) displays the GO Raman bands and those belonging to silicon ~515 and 950 cm −1 . The sharp band at 515 cm −1 could be assigned to TO vibration of Si–Si bond [ 42 ], the red shift from the assigned value of bulk silicon (~520 cm −1 ) could be attributed to the presence of nanocrystals in the nanowire [ 43 ]. The low intensity Raman band at 950 cm −1 appears to correspond to nanosized silicon, as reported by Meier et al [ 44 ], however, the HR-TEM analysis of prepared material revealed that polycrystalline nanoparticles composed of Si and SiC were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…To reveal the mechanism of etch resistance of UV-curable resist, the chemical composition of UV-curable resist was analysed before and after the O 2 plasma etching process by using XPS. The chemical make-up of the top-layer film is analysed by XPS up to a depth of 5-8 nm [9]. The XPS spectra of the UV-curable resist before oxygen plasma etching (Fig.…”
Section: Resultsmentioning
confidence: 99%